ANALYSIS OF REPUTATION, FACILITIES, AND PRICE ON STUDENTS' DECISIONS TO CHOOSE THE MANAGEMENT STUDY PROGRAM AT MUHAMMADIYAH UNIVERSITY OF SIDOARJO - Dhea Wulan Arianti; Mas Oetarjo; Dewi Komala Sari (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - The purpose of this study was to determine the effect of reputation, facilities, and price on students' decisions to choose the Management Study Program at the University of Muhammadiyah Sidoarjo.METHODOLOGY - This study uses a quantitative approach and the population is all active students of the Management Study Program in 2021-2024. The sampling technique for this study uses the probability sampling method with a simple random sampling technique and with a total of 330 respondents. The criteria are active students of the Management Study Program in 2021-2024. The data collection technique in this study is primary data using an online questionnaire. The data analysis technique in this study uses multiple linear regression analysis with SPSS version 25.FINDING - The results of the study prove that reputation influences student decisions, facilities influence student decisions, and prices influence student decisions in choosing the Management Study Program at Muhammadiyah University of Sidoarjo